Synthesis of freestanding binder- and additive-free carbon nanofiber with graphene-wrapped Nb2O5 composite anode for lithium-ion batteries. (20th October 2021) - Kim, Doo-Won; Kim, So Yeun; Yang, Kap Seung
Abstract: Niobium pentoxide (Nb2 O5 )-based materials have attracted significant interest for application in diverse fields. Unfortunately, the employment of these materials as electrodes of lithium-ion batteries (LIBs) is limited by several inherent drawbacks. The present study demonstrated the synthesis of composites comprising homogeneous graphene-wrapped niobium pentoxide (GNbO) encapsulated in carbon nanofibers (CNFs) for utilization as binder- and additive-free anodes in LIBs. The composites were synthesized via electrospinning and subsequent carbonization; the presence of graphene (G) ensured the homogenous dispersion of the Nb2 O5 particles in the CNF matrix. The CNFs formed a highly conductive network that resulted in high physical flexibility, electrical conductivity, and structural stability during charge–discharge cycles, thereby facilitating rapid ion/electron transmission. Consequently, the CNF/GNbO composite anodes exhibited outstanding electrochemical performances. CNF/GNbO_5 (one of the synthesized composites with an Nb2 O5 concentration of 5 wt% relative to GO) delivered a specific capacity of 361 mAh g −1 after 100 cycles, corresponding to a capacity retention of 58.3%. In addition, it exhibited an excellent rate capability with a capacity of 317 mAh g −1 at 10 C. The outcomes of the present study will facilitate the extensive application of the synthesized composites as high-performance anodes in next-generation LIBs.